Thinking like a nurse: the power of drama on nursing students' professional education and communication skills - Gunay, Ulviye; Dertli, Semiha (Ani Publishing, 2024)
Various educational methods are used in nursing education to develop the knowledge and skills suitable for the profession. Drama is a teaching technique that aims for students to acquire knowledge, skills, and understanding about human relations by using game techniques. This study was conducted to determine the power of drama on nursing students' professional education and communication skills. This study was carried out using a phenomenological method with nursing students comprising the five focus groups. During focus interviews, 28 students answered whether through drama-method learning experience and drama has affected personal development. The content analysis method was used in the interpretation of the data. As a result of the content analysis conducted in this study, four main themes and nine subthemes were determined. Themes are; 1. Learning (effective learning, learning by having fun); 2. Confidence (improvement in selfshowed that education through the drama method improves the learning of nursing students. Education through the drama method enables nursing students to learn effectively. This research has provided valuable information on the use of drama method.
Keywords: Nursing education; Interactive education; Drama; Learning; Communication; Nursing students